2015
DOI: 10.1002/jcb.25068
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor‐α‐Induced Protein‐8 Like‐2 (TIPE2) Upregulates p27 to Decrease Gastic Cancer Cell Proliferation

Abstract: The pathogenesis of gastric cancer is not completely understood. Tumor necrosis factor-α-induced protein-8 like-2 (TIPE2) has recently been identified as a novel negative regulator gene of the immune system, and studies in mice and humans have suggested its inhibitory action in both inflammation and cancer. In this study, we examined the expression levels of TIPE2 in human gastric cancer tissues and also samples of paraneoplastic control tissue, and found that TIPE2 expression was reduced in gastric cancer. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 43 publications
(52 reference statements)
4
46
1
Order By: Relevance
“…52 In neoplastic studies, TIPE2 expression has been found to be decreased or completely lost in human hepatic cancer, 23 and reduced TIPE2 expression is associated with metastasis. It is also downregulated in gastric cancer tissues, 53 NSCLC tumors 54 and small cell lung cancer tumors, 55 and the levels of TIPE2 inversely correlate with NSCLC TNM staging. 54 Moreover, reduced TIPE2 expression is associated with metastasis of hepatic cancer.…”
Section: Tipe2 Is a Negative Regulator Of Immunity And Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…52 In neoplastic studies, TIPE2 expression has been found to be decreased or completely lost in human hepatic cancer, 23 and reduced TIPE2 expression is associated with metastasis. It is also downregulated in gastric cancer tissues, 53 NSCLC tumors 54 and small cell lung cancer tumors, 55 and the levels of TIPE2 inversely correlate with NSCLC TNM staging. 54 Moreover, reduced TIPE2 expression is associated with metastasis of hepatic cancer.…”
Section: Tipe2 Is a Negative Regulator Of Immunity And Inflammationmentioning
confidence: 99%
“…68 In contrast, TIPE2 overexpression induced cell death and inhibited Ras-mediated tumorigenesis in mice. 23 In gastric cell lines, increased TIPE2 expression decreased cell proliferation by upregulating N-ras and p27 expression, 53 the latter of which is mediated by interferon regulatory factor 4 via NF-κB; 69 TIPE2 has also been found to regulate AKT and ERK1/2 signaling in these cells 70 as well as GSK3β and downstream β-catenin translocation. 71 Finally, TIPE appears to regulate angiogenesis in retinal pigment epithelium by inhibiting VEGF.…”
Section: Tipe2 Is a Negative Regulator Of Immunity And Inflammationmentioning
confidence: 99%
“…Decreased TIPE2 expression were previously reported in a number of tumors such as hepatocellular carcinoma (HCC), gastric cancer, glioma and prostate cancer [14, 15, 17, 32]. However, increased TIPE2 expression was also observed in some specific tumors including colorectal cancer (CRC), non-small cell lung cancer (NSCLC) and skin squamous cancer [16, 33, 34].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that TIPE2 may function as a tumor suppressor by inhibiting several classic oncogenic signaling pathways [15, 17]. Our previous research demonstrated that TIPE2 suppressed the migration and invasion of HCC and NSCLC cells by inhibiting Rac1 [14, 16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation